A Research on Producer Reasons for Participation into Agricultural Fairs - Özdal Köksal; Duygu Aktürk; Sema Gün (Turkish Journal of Agriculture: Food Science and Technology)
Ever-developing agricultural technologies and progress in communication science increase competition and globalization in converge countries. Agricultural fairs offer ambient to bring producers and input-suppliers of agriculture together at certain places and times. They offer direct and efficient information about new technologies to producers. German Agricultural Society and Leader Farmer Association have jointly organized outdoor fairs in Turkey since 2010. Agriculture Days Fair is one of the most important events among these jointly organized fairs. This study was conducted to determine the reasons for producers’ participation in these fairs held in 2015 and 2017 and to determine the effects of socio-economic characteristics of the producers on their reasons for participation in these fairs. A total of 589 questionnaires were made in this study (250 in May 2015 fair and 339 in August 2017 fair). The same questionnaire forms were used in both years. CHAID analysis technique was employed in analyzing data gathered from the producers. It was observed that producers generally participated in agricultural fairs just for the excursion or spent time with their families at weekends. However, it was also determined that the producers were informed about the agricultural fairs by producer organizations and Leader Farmer Association participated in the fairs to promote a new products or to give information about new technologies and inputs. It can be suggested that beyond informing producers about the fairs, Leader Farmer Association formed within the scope of Leader Farmer Project initiated with the support of German Agricultural Society (DLG) should convey information about how important the fairs are in the acquaintance with introducing new information and technologies.